The heat pump system for ventilation and air conditioning inside the production area with an excessive internal moisture generation - Bezrodny, M.K.; Misiura, T.O. (of the E.A. Buketov KarU publ., 2020)
The paper studies application feasibility and energy efficiency of the ventilation and air conditioning heat pump system for maintaining comfort conditions inside the production area with an excessive internal moisture generation during the warm season. In this regard, a thermodynamic analysis of a heat pump system with a partial exhaust air recirculation and a variable ratio of fresh outside air was carried out. Numerical analysis was then done to estimate the influence of changes in the environment temperature and relative humidity and the characteristics of the ventilation and air conditioning object on the system parameters. This allowed to determinepotential capabilities of this system to maintain comfortable conditions in the production area. It was also shown that the required additional cooling of the supply air at the entrance to the premise for air conditioning demands can be determined by a simple coefficient and its calculation method is provided in the article. The heat pump system of temperature and humidity maintenance has the highest energy efficiency in the zone of relatively low environment temperatures and largely depends on the relative humidity of the outside air. This suggests that the studied system is suitable for application in countries with temperate continental climate.
Keywords: heat pump system; ventilation; air conditioning; refrigeration efficiency; recirculation; comfortable conditions; production area; temperate continental climate